Pengaruh Integrasi Rantai Pasok terhadap Kinerja Perusahaan : Studi pada Usaha Mikro Makanan dan Minuman di Kota Cilegon - Musannatunnawar, Musannatunnawar; Moh. Mukhsin (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
This study aims to examine how supply chain integration efficiency affects the performance of micro businesses in Cilegon. A total of 90 respondents, consisting of managers and owners of micro businesses, were sampled for this study. Data collection was conducted by distributing questionnaires to each respondent. The data analysis technique used was Partial Least Squares (PLS). The results showed that company performance was positively influenced by supplier integration, internal integration, and consumer integration implemented in these micro businesses. In other words, company performance was influenced by the supply chain integration applied within the company. These findings underscore the importance of a coordinated supply chain integration strategy to improve the efficiency and competitiveness of micro-enterprises, particularly in addressing the challenges facing the small and medium-sized enterprise sector. Therefore, it is recommended that micro-enterprises in Cilegon continue to improve supply chain integration to boost their performance and sustainability. Therefore, it is recommended for micro-enterprises in Cilegon to continue improving the integration aspects of their supply chains, by strengthening relationships with suppliers, improving internal coordination, and better understanding consumer needs to boost company performance and ensure the long-term sustainability of their businesses.